Conscientiousness in Game-Based Learning. (October 2020) - Yi, Liu; Zhou, Qiqi; Xiao, Tan; Qing, Ge; Mayer, Igor
Background. An increasing number of studies support a mediating influence ofpersonality on video-game preferences and player experiences, and in particular, traits associated with playfulness, such as extraversion. Educational institutions, however, tend to reward serious personality traits, such asconscientiousness . Aim. To discern how students respond toGame-Based Learning (GBL) in the classroom, and to understand if and how conscientiousness mediates GBL, we performed a field study at a leading university of technology in northeastChina . Method. In May 2019, 60 bachelor and executive students inpublic-administration studies consecutively played two digital serious games, TEAMUP (multiplayer) and DEMOCRACY3 (single player). Data accrued through surveys with pregame measurements of personality (conscientiousness), mediating factors (motivation, player experience ), learning effectiveness (cognitive and non-cognitive learning), and GBL acceptance. Results. Analysis showed a strong overall learning effect for both games. Conscientiousness significantly related to cognitive learning in both games and noncognitive learning in the multiplayer game only. Conscientiousness also significantly related to player experiences in the multiplayer game. Furthermore, the conscientiousness facet ofperfectionism was a dominant factor in player experience and learning. We discuss the findings in light of several aspects around GBL that require more attention and research, especially that, alongside other factors, conscientiousness may be an important dimension to consider in the design and implementation of GBL in education, and GBL can have a positive role in themodernization of education in non-Western countries.